Identification and Simultaneous Determination of the Main Toxical Pyrrolizidine Alkaloids in a Compound Prescription of Traditional Chinese Medicine: Qianbai Biyan Tablet. (9th September 2021) - Yang, Mengting; Tan, Daopeng; Lu, Anjing; Qin, Lin; Wang, Changhong; Ling, Hua; Lu, Yanliu; He, Yuqi
Abstract : Qianbai biyan tablet (QT) is a compound prescription of traditional Chinese medicine which is used to treat nasal congestion, rhinitis, and nasosinusitis, with Senecio scandens as its main plant material. Several pyrrolizidine alkaloids (PAs) were reported in Senecio scandens and others of Senecio species. Although Senecio scandens is assigned as the legal plant material of QT, whether replaced use of it by other Senecio plants can bring toxicity is unknown because of the lack of quantitative data about toxic PAs between different Senecio species. In the present study, adonifoline, senkirkine, and another PA presumed as emiline have been identified in QT; however, there was no senecionine detected in all tablets. PA contents in QTs varied in different companies and different batches. Adonifoline existed only in Senecio scandens, and senecionine was detected in all eight Senecio plants investigated in the present study. Data showed that replaced use of Senecio scandens with a low level of senecionine by other Senecio plants such as Senecio vulgaris containing a high level of senecionine is advertised to be forbidden. Data of the present study may be used as a reference to make new drug quality regularity and recommendation guideline for the safety of QT.